(untitled) - Akaha, Tsuneo (Honolulu, 1985)
The present study and explains the Japanese government's decision-making process leading to its final decisions in January and March 1977, respectively, to extend the country's territorial ses limt from three to twelve miles and to establish its 200-miles fishery zone.
Keywords: Khu kinh tế (luật Hàng hải),Economic zones (Maritime law); Nhật Bản,Japan